Effect of a ketogenic diet on pain and quality of life in patients with lipedema: The LIPODIET pilot study. (21st April 2022) - Sørlie, Vilde; De Soysa, Ann Kristin; Hyldmo, Åsne Ask; Retterstøl, Kjetil; Martins, Catia; Nymo, Siren
Abstract: Background: Lipedema is an underdiagnosed condition in women, characterized by a symmetrical increase in subcutaneous adipose tissue (SAT) in the lower extremities, sparing the trunk. The lipedema SAT has been found to be resistant to diet, exercise and bariatric surgery, in regard to both weight loss (WL) and symptom relief. Current experience indicates that a low carbohydrate and high fat (LCHF‐diet) might have a beneficial effect on weight and symptom management in lipedema. Objective: To assess the impact of an eucaloric low carbohydrate, high fat (LCHF)‐diet on pain and quality of life (QoL) in patients with lipedema. Methods: Women diagnosed with lipedema, including all types and stages affecting the legs, (age 18–75 years, BMI 30–45 kg/m 2 ) underwent 7 weeks of LCHF‐diet and, thereafter 6 weeks of a diet following the Nordic nutrition recommendations. Pain (visual analog scale) and QoL (questionnaire for lymphedema of the limbs), weight and body composition were measured at baseline, week seven and 13. Results: Nine women (BMI: 36.7 ± 4.5 kg/m 2 and age: 46.9 ± 7 years) were recruited. The LCHF diet induced a significant WL −4.6 ± 0.7 kg (−4.5 ± 2.4%), p  < 0.001 for both, and reduction in pain (−2.3 ± 0.4 cm, p  = 0.020). No correlation was found between WL and changes in pain at week seven (r = 0.283, p  = 0.460). WL was maintained between week seven and 13 (0.3 ± 0.7 kg, p  = 0.430), but pain returned to baseline levels at week 13 (4.2 ± 0.7 cm, p  = 0.690). A significant increase in general QoL was found between baseline and week seven (1.0 (95% CI (2.0, 0.001)), p  = 0.050) and 13 (1.0 95% CI (2.0, 0.001) p  = 0.050), respectively. Conclusion: A LCHF‐diet is associated with reduction in perceived pain and improvement in QoL, in patients with lipedema. Larger randomized clinical trials are needed to confirm these findings.